Gerakan Gemar Menabung untuk Siswa Sekolah Dasar di Kecamatan Meureubo, Aceh Barat - Budianto Budianto; Rina Maulina; Nani Verawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service aims to provide elementary school students with an understanding of the importance of saving. It is also expected to contribute to educating the younger generation by saving awareness from an early age. By saving each child will learn independently and not depend on their parents. Saving habits will be better if they get encouragement and motivation from their parents. The method of implementing community service is carried out through 'socialization'. Partners in this activity are SDN Peunaga, Meureubo District, West Aceh Regency. The number of students who took part in the activities was 54 people, consisting of 11 students in Class I, 21 in Class II and 22 in Class III. This activity involved lecturers and students from the Accounting Department, University Teuku Umar. The results of this activity are expected to increase saving interest in elementary school students in Meureubo District, West Aceh Regency.